Broadband Internet, Labor Demand, and Total Factor Productivity in Colombia - Ospino, Carlos (World Bank, Washington, DC, 2018)
This paper studies the relationship between information and communication technology, labor demand, and total factor productivity in Colombia. It estimates total factor productivity for the Colombian manufacturing sector using a method that assumes a law of motion where total factor productivity evolves according to an autoregressive process of order 1 as well as with the past use of broadband technologies. Using fixed effects models, the paper estimates the effect of broadband use on the labor demand of different workers, controlling for total factor productivity, capital, and wages. To address the potential endogeneity between broadband adoption and labor demand, the analysis uses state-industry level variation in broadband quality (speed) and intensity of use. The results show a positive association of broadband adoption on labor demand, suggesting that adoption of information and communication technology can offset the employment effects of technological growth. Attempts to identify causal effects using an instrumental variable approach were inconclusive.